Preparation and Evaluation of In-Situ Gel from the Root Extract of Boerhaavia Diffusa in the Treatment of Cataract - Lanjewar, Kalyani; Telgote, Sachi; Shirpurkar, Avantika (Asian Journal of Pharmaceutical Research and Development, 2024)
Cataract remains a significant global health issue, necessitating innovative treatment approaches. This study explores the formulation of an in-situ gel derived from the roots of Boerhaavia diffusa for potential cataract therapy. Boerhaavia diffusa, renowned for its pharmacological properties, offers a promising natural source for ocular drug delivery. The gel formulation is designed to provide sustained drug release and enhanced bioavailability, addressing the limitations of conventional treatments. The preparation method involves extraction of bioactive compounds from Boerhaavia diffusa roots, followed by formulation into a thermo-sensitive in-situ gel using suitable polymers.The roots of Boerhaavia diffusa were collected, washed, and dried before extraction using a suitable solvent system. The obtained extract was then evaluated for its phytochemical composition, including alkaloids, Glycosides, tannin, terpenoid and Saponins, through standard qualitative and quantitative methods.The in-situ gel formulation was prepared using the obtained extract and suitable gelling agents. Various physicochemical parameters of the gel, such as pH, viscosity, Spreadability, and washability, were optimized to ensure stability and efficacy... The findings of this research hold promise for the development of a novel, natural-based therapeutic approach for cataract management, potentially offering improved patient outcomes and quality of life.